Assessing security governance in the UK and Scotland under current arrangements : the first of six events in the ESRC seminar series: Security in Scotland, with or without constitutional change /: the first of six events in the ESRC seminar series: Security in Scotland, with or without constitutional change. ([2013?]) - Neal, Andrew W, 1978-
No abstract available